In-Hive Acaricides Alter Biochemical and Morphological Indicators of Honey Bee Nutrition, Immunity, and Development. Issue 5 (29th September 2018) - Reeves, Alison M; O'Neal, Scott T; Fell, Richard D; Brewster, Carlyle C; Anderson, Troy D
Abstract: The honey bee is a widely managed crop pollinator that provides the agricultural industry with the sustainability and economic viability needed to satisfy the food and fiber needs of our society. Excessive exposure to apicultural pesticides is one of many factors that has been implicated in the reduced number of managed bee colonies available for crop pollination services. The goal of this study was to assess the impact of exposure to commonly used, beekeeper-applied apicultural acaricides on established biochemical indicators of bee nutrition and immunity, as well as morphological indicators of growth and development. The results described here demonstrate that exposure to tau -fluvalinate and coumaphos has an impact on 1) macronutrient indicators of bee nutrition by reducing protein and carbohydrate levels, 2) a marker of social immunity, by increasing glucose oxidase activity, and 3) morphological indicators of growth and development, by altering body weight, head width, and wing length. While more work is necessary to fully understand the broader implications of these findings, the results suggest that reduced parasite stress due to chemical interventions may be offset by nutritional and immune stress.